Draft Genome of the Wheat Rust Pathogen (Puccinia triticina) Unravels Genome-Wide Structural Variations during Evolution. (13th August 2016) - Kiran, Kanti; Rawal, Hukam C.; Dubey, Himanshu; Jaswal, Rajdeep; Devanna, B.N; Gupta, Deepak Kumar; Bhardwaj, Subhash C.; Prasad, P.; Pal, Dharam; Chhuneja, Parveen; Balasubramanian, P.; Kumar, J.; et al.
Abstract: Leaf rust is one of the most important diseases of wheat and is caused by Puccinia triticina, a highly variable rust pathogen prevalent worldwide. Decoding the genome of this pathogen will help in unraveling the molecular basis of its evolution and in the identification of genes responsible for its various biological functions. We generated high quality draft genome sequences (approximately 100- 106 Mb) of two races of P. triticina ; the variable and virulent Race77 and the old, avirulent Race106. The genomes of races 77 and 106 had 33X and 27X coverage, respectively. We predicted 27678 and 26384 genes, with average lengths of 1, 129 and 1, 086 bases in races 77 and 106, respectively and found that the genomes consisted of 37.49% and 39.99% repetitive sequences. Genome wide comparative analysis revealed that Race77 differs substantially from Race106 with regard to segmental duplication (SD), repeat element, and SNP/InDel characteristics. Comparative analyses showed that Race 77 is a recent, highly variable and adapted Race compared with Race106. Further sequence analyses of 13 additional pathotypes of Race77 clearly differentiated the recent, active and virulent, from the older pathotypes. Average densities of 2.4 SNPs and 0.32 InDels per kb were obtained for all P. triticina pathotypes. Secretome analysis demonstrated that Race77 has more virulence factors than Race 106, which may be responsible for the greater degree of adaptation of this pathogen. We also found that genes under greater selection pressure were conserved in the genomes of both races, and may affect functions crucial for the higher levels of virulence factors in Race77. This study provides insights into the genome structure, genome organization, molecular basis of variation, and pathogenicity of P. triticina . The genome sequence data generated in this study have been submitted to public domain databases and will be an important resource for comparative genomics studies of the more than 4000 existing Puccinia species.